2015
DOI: 10.3354/ame01752
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic assessment of viral diversity in Lake Matoaka, a temperate, eutrophic freshwater lake in southeastern Virginia, USA

Abstract: Little is known about the composition and diversity of temperate freshwater viral communities. This study presents a metagenomic analysis of viral community composition, taxonomic and functional diversity of temperate, eutrophic Lake Matoaka in southeastern Virginia (USA). Three sampling sites were chosen to represent differences in anthropogenic impacts: the Crim Dell Creek mouth (impacted), the Pogonia Creek mouth (less impacted) and the main body of the lake (mixed). Sequences belonging to tailed bacterioph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 41 publications
2
30
1
Order By: Relevance
“…The recent development of sequencing technologies has facilitated viral metagenomics (viromics), opening the door to elucidating the vast diversity of uncultured viral genomes and genes (32)(33)(34) and challenging the classical taxonomy of viruses (35). In freshwater systems, early viromics investigations were performed using the 454 sequencing platform, which helped to clarify the uniqueness and diversity of the freshwater virosphere (36)(37)(38)(39)(40). Later, the Illumina sequencing platform allowed >10-fold increases in read throughput and library preparation without the biases of multiple displacement amplification, which facilitated the assembly of much longer viral genomic fragments, including complete viral genomes (41)(42)(43)(44)(45).…”
Section: Introductionmentioning
confidence: 99%
“…The recent development of sequencing technologies has facilitated viral metagenomics (viromics), opening the door to elucidating the vast diversity of uncultured viral genomes and genes (32)(33)(34) and challenging the classical taxonomy of viruses (35). In freshwater systems, early viromics investigations were performed using the 454 sequencing platform, which helped to clarify the uniqueness and diversity of the freshwater virosphere (36)(37)(38)(39)(40). Later, the Illumina sequencing platform allowed >10-fold increases in read throughput and library preparation without the biases of multiple displacement amplification, which facilitated the assembly of much longer viral genomic fragments, including complete viral genomes (41)(42)(43)(44)(45).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their underrepresentation in databases, research has demonstrated that freshwater virus communities contain novel viruses and are distinct from other aquatic virus communities [15-17]. Metagenomics has been used to study virus communities in natural freshwater lakes from the Arctic [18], Canada [19], USA [20,21], Ireland [22], France [17], China [23], and Antarctica [24,25]. With respect to virus communities in eutrophic lakes, studies by Green et al [20], Skvortsov et al [22], and Ge et al [23] revealed virus communities dominated by Caudovirales in the epilimnion of eutrophic lakes in China, USA, and Ireland, respectively, but other dsDNA viruses, unclassified bacteriophages, and ssDNA viruses were also detected albeit at lower abundances.…”
Section: Introductionmentioning
confidence: 99%
“…Metagenomics has been used to study virus communities in natural freshwater lakes from the Arctic [18], Canada [19], USA [20,21], Ireland [22], France [17], China [23], and Antarctica [24,25]. With respect to virus communities in eutrophic lakes, studies by Green et al [20], Skvortsov et al [22], and Ge et al [23] revealed virus communities dominated by Caudovirales in the epilimnion of eutrophic lakes in China, USA, and Ireland, respectively, but other dsDNA viruses, unclassified bacteriophages, and ssDNA viruses were also detected albeit at lower abundances. Roux et al [26] focused on the virophage and NCLDV communities in a eutrophic freshwater lake in USA, and observed highly dynamic virophage communities lacking any apparent annual or seasonal patterns of abundance.…”
Section: Introductionmentioning
confidence: 99%
“…When 39 viromes from eight freshwater lakes and reservoirs (Roux et al, 2012;Tseng et al, 2013;Green et al, 2015;Mohiuddin and Schellhorn, 2015;Skvortsov et al, 2016;Watkins et al, 2015) were analyzed using the same method as that for Lake Soyang, contribution of P19250A among the virus-assigned reads ranged from 0.14% to 6.49% (Supporting Information Table S4). P19250A-assigned reads especially showed the highest proportion in the virome of Lough Neagh (Skvortsov et al, 2016), at 6.49%, followed by the virome of Lake Matoaka (open) (Green et al, 2015), at 5.50% (Table 1 and Supporting Information Table S4). P19250A ranked the first among freshwater phages for both samples, while most other highly assigned viruses were of marine origin, as was observed in the Lake Soyang viromes.…”
Section: Crucial Role Of P19250a In Analyses Of Freshwater Viromesmentioning
confidence: 99%
“…Only very recently, genome sequences of phages that were suggested to infect the acI clade were assembled from deeply sequenced freshwater metagenomes (Ghai et al, 2017). In several freshwater viral metagenome studies performed recently, this lack of representative freshwater phages has hampered proper taxonomic and functional interpretation of freshwater viromes (Bruder et al, 2016), and has resulted in many freshwater virome reads being assigned to marine phages (Green et al, 2015;Skvortsov et al, 2016).…”
Section: Introductionmentioning
confidence: 99%